The Nonuniform Distribution of Stylolite in Bioclastic Limestones and Its Influence on Reservoir Petro-Physical Properties—A Case Study of the Mishrif Formation from the Ah Oilfield - Jiacheng Xu; Ya Deng; Meiyan Fu; Rui Guo; Pei Chen; Guanghui Duan; Ruicheng Ma (Energies, 2022)
The effect of stylolite caused by the pressure dissolution process on the reservoir petro-physical properties is still controversial. This study aims to reveal the effect of stylolite on the porosity and permeability of packstone and wackestone in the Mishrif Formation from the Ah oilfield in the Middle East. Based on the observation of thin sections and cores, X-ray diffraction analysis and porosity and permeability measurement, the lithofacies, diagenesis and patterns of stylolites have been investigated. There are six lithofacies in the Mi4 member, including bivalve green algae packstone, green algae packstone, pelletoid green algae packstone, echinoderm packstone, rudist packstone, planktonic foraminifera wackestone and bioclastic wackestone. The mechanical compaction and pressure dissolution could be observed in these lithofacies, with the development of dissolution seams and stylolites. The density of stylolite has a relationship with the lithofacies and early cementation. The boundary between the echinoderm packstone and the green algae packstone mostly developed as stylolites. There are four types of stylolite on the cores. Type A is the wave-like stylolite developed at the boundary between the echinoderm packstones and green algae packstones. Type B is the zigzag stylolite with high amplitude in the green algae packstones. Type C is the stylolites with low amplitude in the bioclastic wackestones. Type D is the high-angle stylolite, which is oblique to the bedding plane. The permeability of reservoir rocks could be improved by dissolution along the type B stylolite, while the type A and type C stylolite have little effect on permeability. The permeability of green algae packstone and echinoderm packstone will decrease with the development of stylolites. The porosity and permeability of bivalve green algae packstone will decrease after stylolitization, resulting from the relatively high density of stylolite. The physical properties of bioclastic wackestone could be improved by the bioturbation and ...